Multispecies genotype × environment interaction for turfgrass quality in five turfgrass breeding programs in the southeastern United States. Issue 5 (17th February 2021) - Gouveia, Beatriz Tomé; Rios, Esteban Fernando; Nunes, José Airton Rodrigues; Gezan, Salvador A.; Munoz, Patricio R.; Kenworthy, Kevin E.; Unruh, J. Bryan; Miller, Grady L.; Milla‐Lewis, Susana R.; Schwartz, Brian M.; Raymer, Paul L.; Chandra, Ambika; et al.
Abstract: In breeding programs, superior parental genotypes are used in crosses to generate novel genetic variability for new selection cycles. Genotypes are usually more adapted to environments where the breeding program is located, since selections are performed under specific agroecosystems. Thus, the objective of this study was to evaluate the performance of bermudagrass ( Cynodon Rich. species), St. Augustinegrass [ Stenotaphrum secundatum (Walter) Kuntze], seashore paspalum ( Paspalum vaginatum Sw.), and zoysiagrass ( Zoysia Willd. species) breeding lines from five different breeding programs (North Carolina State University, Oklahoma State University, Texas A&M University System, University of Florida, and University of Georgia) across the southeastern United States. Three breeding nurseries for each species were evaluated for 2 yr at eight locations: Citra and Hague, FL; College Station and Dallas, TX; Griffin and Tifton, GA; Stillwater, OK; and Jackson Springs, NC. Turfgrass quality (TQ) was evaluated (rated on a 1–9 scale) across repeated measurements over time. Data were analyzed using mixed models, and principal component analyses were performed using predicted genotypic values. The narrowest range in variation for TQ performance was observed in seashore paspalum breeding lines, whereas greater variation was observed for St. Augustinegrass and zoysiagrasses. St. Augustinegrass presented the lowest genotype × environment interaction in all nurseries. Specific adaptability was not observed for the lines developed by different breeding programs, with the exception of the bermudagrass lines from Oklahoma State University in Nursery 3.